Emergence of ISAba1 harboring carbapenem-resistant Acinetobacter baumannii isolates in Pakistan. (November 2017) - Khurshid, Mohsin; Rasool, Muhammad Hidayat; Ashfaq, Usman Ali; Aslam, Bilal; Waseem, Muhammad
Aim: The ISAba1 insertion sequence supports the overexpression of various oxacillinases genes by providing promoter and therefore, confers carbapenem resistance. The study aimed to determine the clonal diversity, genetic attributes of carbapenem resistance and the role of ISAba1 in the expression of oxacillinases genes among Acinetobacter baumannii clinical isolates.Materials & methods: PCR was performed to amplify various antimicrobial resistance determinants and ISAba1 insertion elements in 137 A. baumannii clinical isolates.Results: The bla OXA51 and bla OXA23 -like genes and ISAba1 upstream to these genes were found in almost all multidrug-resistant isolates belonging to multiple clones.Conclusion: This is the first comprehensive study from Pakistan that highlighted the emergence of ISAba1 harboring carbapenems resistant A. baumannii stains in tertiary care hospitals. Graphical Abstract: